Role of the Human Cytomegalovirus Major Immediate-Early Promoter's 19-Base-Pair-Repeat Cyclic AMP-Response Element in Acutely Infected Cells - Keller, M. J. (American Society for Microbiology, 2003)
Prior studies have suggested a role of the five copies of the 19-bp-repeat cyclic AMP (cAMP)-response element (CRE) in major immediate-early (MIE) promoter activation, the rate-limiting step in human cytomegalovirus (HCMV) replication. We used two different HCMV genome modification strategies to test this hypothesis in acutely infected cells. We report the following: (i) the CREs do not govern basal levels of MIE promoter activity at a high or low multiplicity of infection (MOI) in human foreskin fibroblast (HFF)- or NTera2-derived neuronal cells; (ii) serum and virion components markedly increase MIE promoter-dependent transcription at a low multiplicity of infection (MOI), but this increase is not mediated by the CREs; (iii) forskolin stimulation of the cAMP signaling pathway induces a two- to threefold increase in MIE RNA levels in a CRE-specific manner at a low MOI in both HFF- and NTera2-derived neuronal cells; and (iv) the CREs do not regulate basal levels of HCMV DNA replication at a high or low MOI in HFF. Their presence does impart a forskolin-induced increase in viral DNA replication at a low MOI but only when basal levels of MIE promoter activity are experimentally diminished. In conclusion, the 19-bp-repeat CREs add to the robust MIE promoter activity that occurs in the acutely infected stimulated cells, although the CREs' greater role may be in other settings.